1994
DOI: 10.1007/bf00967329
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate receptor-driven activation of transcription factors in primary neuronal cultures

Abstract: We have used primary neuronal cultures prepared from fetal cerebral hemispheres to investigate the effects of different glutamate receptor agonists and antagonists on the expression of transcription factor encoding genes, such as c-fos, fosB, c-jun, junB, junD, c-myc, and zif/268. The addition of glutamate (100 microM) to the culture medium rapidly activated c-fos, fosB, c-jun, junB and zif/268 gene expression, reaching the maximal level at 30-60 minutes for zif/268 and at 60 minutes for the other genes. The o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
2

Year Published

1996
1996
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 43 publications
0
19
0
2
Order By: Relevance
“…Little is known about the mechanisms by which EGR-1 contributes to long-term synaptic plasticity, memory consolidation, and reconsolidation. In cultured neurons, both glutamatergic signaling (Condorelli et al 1994) and L-type voltage-gated calcium channels (Murphy et al 1991) have been shown to regulate EGR-1 expression. Further, EGR-1, along with the nuclear transcription factors Elk-1 and CREB, have been shown to be regulated by ERK/MAPK signaling during long-term potentiation (LTP) in the dentate gyrus (Davis et al 2000), suggesting that one or both of these transcription factors plays a critical role in ERK-driven EGR-1 transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the mechanisms by which EGR-1 contributes to long-term synaptic plasticity, memory consolidation, and reconsolidation. In cultured neurons, both glutamatergic signaling (Condorelli et al 1994) and L-type voltage-gated calcium channels (Murphy et al 1991) have been shown to regulate EGR-1 expression. Further, EGR-1, along with the nuclear transcription factors Elk-1 and CREB, have been shown to be regulated by ERK/MAPK signaling during long-term potentiation (LTP) in the dentate gyrus (Davis et al 2000), suggesting that one or both of these transcription factors plays a critical role in ERK-driven EGR-1 transcription.…”
Section: Discussionmentioning
confidence: 99%
“…In cultured cortical neurons (Condorelli et al, 1994;Murphy et al, 1991a,b) or primary cultures containing both cortical and striatal neurons (Vaccarino et al, 1993), NMDA receptor activation will induce c-fos expression. Likewise, in primary hippocampal cultures, NMDA receptor activation results in both CREB phosphorylation and c-fos expression (Bading et al, 1993(Bading et al, , 1995.…”
Section: Introductionmentioning
confidence: 97%
“…In primary cultures of cortical and striatal neurons, activation of NMDA receptors results in induction of c-fos, fosB, c-jun, and junB mRNA (Vaccarino et al, 1992;Condorelli et al, 1994). Glutamate stimulation also results in an NMDA receptordependent increase in AP-1-binding activity in cultured neurons (Condorelli et al, 1994).…”
mentioning
confidence: 99%
“…In primary cultures of cortical and striatal neurons, activation of NMDA receptors results in induction of c-fos, fosB, c-jun, and junB mRNA (Vaccarino et al, 1992;Condorelli et al, 1994). Glutamate stimulation also results in an NMDA receptordependent increase in AP-1-binding activity in cultured neurons (Condorelli et al, 1994). In vivo stimulation of NMDA receptors by intrastriatal injection of quinolinic acid results in the induction of Fos protein in the majority of striatal projection neurons (Berretta et al, 1992).…”
mentioning
confidence: 99%